Obi, gerbil on the loose! - Delaney, M. C. (Michael Clark) (New York : Dutton Children Books, 2008)
Obi the gerbil must fend for herself in a dangerous household, consisting of a dog, three cats, a parrot, and a mouse hidden in the attic, when the Armstrongs go on vacation and instructions for taking care of Obi get lost.
4-6.
740
Keywords: Gerbils -- Fiction; Pets -- Fiction; Animals -- Fiction; Self-confidence -- Fiction; Adventure fiction